A new power/cooling cogeneration system using R1234ze(E)/ionic liquid working fluid. (25th February 2020) - Song, Chang; Liu, Xiangyang; Ye, Zheng; He, Maogang
Summary: A novel power/cooling system integrated with organic Rankine cycle and absorption‐compression refrigeration cycle was proposed in order to realize the cascade utilization of low‐grade energy. In the proposed system, R1234ze(E) (trans‐1, 3, 3, 3‐tetrafluoropropene) is used as the working fluid for the organic Rankine cycle subsystem and the binary mixtures of R1234ze(E) with three ionic liquids [HMIM][BF4 ], [EMIM][BF4 ] and [OMIM][BF4 ] are used as working fluid for absorption‐compression refrigeration cycle subsystem due to their superior environmental protection property and physicochemical property. Moreover, in order to recover the heat of the exhaust gas from turbine in organic Rankine cycle subsystem, the exhaust gas is mixed with R1234ze(E)/ionic liquid solution directly in desorber, while the heat of refrigerant from desorber is recovered to reduce the heat load of condenser. The proposed system has much higher energy and exergy efficiency and lower heat load of condenser than reference system. Under specific conditions, increases of 0.24 and 0.07 in thermal efficiency and exergy efficiency of reference system can be achieved. The effect of distribution ratio, expansion ratio, heat source temperature, condensation temperature, generation temperature, evaporation temperature and compression ratio were analyzed for better design in actual application. Abstract : New power/cooling cogeneration system using R1234ze(E)/ionic liquid working fluid.